2017
DOI: 10.1007/s12602-017-9341-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification of Lactobacillus mucosae AN1 and its Antilisterial Peptide Purification and Characterization

Abstract: Lactobacillus mucosae strain AN1 isolated from sheep milk and characterized for its probiotic suitability. In vitro evaluation of critical gut endurance properties of this strain were assessed by different screening methods such as bile salt, gastric acid, lysozyme tolerance assays, hemolytic, cholesterol reduction properties, and HT-29 cell line adhesion assay. Antibacterial peptide from this strain was purified using ammonium sulphate precipitation, gel filtration chromatography and reverse-phase HPLC. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Similar studies showed that Pediococcus pentosaceus CE65 able to survive at 0.3% bile salts (Manini et al, 2016). Another study with L. mucosae AN1 also showed resistance towards bile salts from 0.1 to 0.7% (Repally et al, 2018).…”
Section: Discussionmentioning
confidence: 53%
“…Similar studies showed that Pediococcus pentosaceus CE65 able to survive at 0.3% bile salts (Manini et al, 2016). Another study with L. mucosae AN1 also showed resistance towards bile salts from 0.1 to 0.7% (Repally et al, 2018).…”
Section: Discussionmentioning
confidence: 53%
“…Probiotic bacteria Lactobacillus mucosae (GenBank, KM068788), Lactobacillus fermentum (GenBank, KM068787) were isolated from sheep milk and fermented rice gruel, respectively (Repally et al, 2017). These probiotic strains were used for the treatment of inflammation induced in hind rats paw tissues.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial strains were isolated aseptically from the gut content of indigenous country chicken and South Indian fermented tomato pickle (homemade) by spreading samples over MRS agar plates (a selective media to obtain Gram positive LAB only) and incubated anaerobically at 37°C. Several bacterial colonies were observed on the MRS agar plates after 42 h of incubation and randomly picked colonies were subjected for antimicrobial activity test by well diffusion method according to Repally et al (2018). Bacterial colonies were grown in MRS broth overnight at 37°C in an incubator shaker.…”
Section: Isolation and Identification Of Bacterial Isolatesmentioning
confidence: 99%
“…Further, the selected bacterial isolates were identified by 16s DNA sequencing. Universal 16S rRNA primers were used to amplify the 16S rRNA genes and the PCR conditions were implemented according to Repally et al (2018). The identified strains were labeled as B. subtilis CS (MG694567), Bacillus tequilensis CL (MG694566) and, Weissella cibaria p3B (MH473733).…”
Section: Isolation and Identification Of Bacterial Isolatesmentioning
confidence: 99%